2014
DOI: 10.3109/02713683.2014.941071
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collagen Cross-Linking Procedure on the Material of Intracorneal Ring Segments

Abstract: Our results suggest crosslinking reaction in ICRS material. This should be taken into consideration prior to any CXL treatment of post ICRS-implanted cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…An AFM image after the creep test showed that collagen fibers were aligned in the direction that applied the stress C. In the cycle test, the whole specimen was extended by approximately 20% D, E. An AFM image after the test showed that collagen fibers were also aligned in the direction that applied the stress F. The growth of collagen fibers by the creep test was more advanced than that by the cycle test. The white arrows on the figures show the tensile direction collagen molecules, and the chemical substances produced during each cross-linking reaction have also been identified [36][37][38]. Due to the detailed understanding of the regenerative process of the tendon, it is necessary to characterize the initial process of the structural change in tendon gel specimens and the normal tendon of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An AFM image after the creep test showed that collagen fibers were aligned in the direction that applied the stress C. In the cycle test, the whole specimen was extended by approximately 20% D, E. An AFM image after the test showed that collagen fibers were also aligned in the direction that applied the stress F. The growth of collagen fibers by the creep test was more advanced than that by the cycle test. The white arrows on the figures show the tensile direction collagen molecules, and the chemical substances produced during each cross-linking reaction have also been identified [36][37][38]. Due to the detailed understanding of the regenerative process of the tendon, it is necessary to characterize the initial process of the structural change in tendon gel specimens and the normal tendon of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cross-linking models [36][37][38], the FT-IR spectrum is explained as follows: the first cross-linking reaction is known as an aldol condensation cross-linking reaction. In this reaction, a saturated fatty acid aldehyde group (-CHO group) was formed [36], and a peak indicating the presence of the -CHO group was confirmed near 1750 cm -1 at an arrowed peak (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in the same concept Sideroudi et al reported that CXL procedure leads to the crosslinking effect not only of the corneal collagen but of the ICRS core material as well. This finding should be taken into consideration prior to any CXL treatment of post ICRS implanted cornea 15. …”
mentioning
confidence: 84%
“…Sideroudi et al [ 136 ] assessed the impact of corneal CXL on the material properties of ICRS. They found that an amount of riboflavin solution was absorbed into the samples of ICRS analyzed after CXL procedure.…”
Section: Combined Proceduresmentioning
confidence: 99%